Multiple Structural and Functional Abnormalities in the P450 Aromatase Expressing Transgenic Male Mice Are Ameliorated by a P450 Aromatase Inhibitor - Li, Xiangdong (American Society for Investigative Pathology, 2004)
The present study was undertaken to analyze the effect of a P450 aromatase inhibitor (finrozole) on 4-month-old transgenic mice expressing human P450 aromatase (P450arom) under the human ubiquitin C promoter (AROM+). AROM+ mice present several dysfunctions, such as adrenal and pituitary hyperplasia, cryptorchidism, Leydig cell hypertrophy and hyperplasia, and gynecomastia. The present study demonstrates that these abnormalities were efficiently treated by administration of a P450arom inhibitor, finrozole. The treatment normalized the reduced intratesticular and serum testosterone levels, while those of estradiol were decreased. The body weight and several affected organ weights were normalized with the treatment. Histological analysis revealed that both the pituitary and adrenal hyperplasia were diminished. Furthermore, the cryptorchid testes present in the untreated AROM+ males descended to scrotum, 4 to 15 days after inhibitor treatment. In addition, the disrupted spermatogenesis was recovered and qualitatively complete spermatogenesis appeared with the inhibitor treatment. This was associated with normalized structure of the interstitial tissue, as analyzed by immunohistochemical staining for Leydig cells and macrophages. One of the features was that the Leydig cell hypertrophy was markedly diminished in the treated mice. AROM+ mice also present with severe gynecomastia, while the development and differentiation of the mammary gland in AROM+ males was markedly diminished with the inhibitor treatment. Interestingly, the mammary gland involution was associated with the induction of androgen receptor in the epithelial cells, while estrogen receptors were still detectable in the epithelium. The data show that AROM+ mouse model is a novel tool to further analyze the use of P450arom inhibitors in the treatment of the dysfunctions in males associated with misbalanced estrogen to androgen ratio, such as pituitary adenoma, testicular dysfunction, and gynecomastia.